Efficacy of continuous infusion of ceftazidime for patients with neutropenic fever after high-dose chemotherapy and peripheral blood stem cell transplantation - Egerer, Gerlinde; Goldschmidt, Hartmut; Salwender, Hans; Hegenbart, Ute; Ehrhard, Ingrid; Haas, Rainer; Ho, Anthony Dick (International journal of antimicrobial agents, 2000)
Neutropenia is an important complication of high-dose chemotherapy (HDCT). Neutropenic patients presenting with fever are routinely hospitalized for treatment with broad-spectrum antibiotics. Neutropenia up to 10 days is associated with a low-risk profile, and antimicrobial therapy administered on an outpatient basis might be an alternative to admission to hospital. This prospective study evaluates the safety of a continuous infusion of ceftazidime in neutropenic patients after HDCT and peripheral blood stem cell transplantation (PBSCT). From September 1995 to October 1999, 81 patients received a 2 g intravenous bolus of ceftazidime, followed by a 4 g continuous infusion per 24 h of ceftazidime using a portable infusion pump. If the fever persisted for 72 h, a glycopeptide antibiotic was added. The median patients’ age was 44 years. Fifty-two of 81 patients (64%) responded to the monotherapy with ceftazidime. After addition of a glycopeptide antibiotic, a further 17 patients (21%) became afebrile. The causes of fever were septicaemia in 11 patients, pneumonia in two and fever of unknown origin in 68 patients. Fifty-eight episodes (72%) were successfully managed by outpatient treatment alone. The reason for admission to hospital was the change to imipenem/cilastin, which had to be administered three times per day (12 patients), severe mucositis with parenteral nutrition (eight patients), or a Karnovsky index ≤60 (three patients). In six of these cases, outpatient treatment was resumed after a brief period of in-patient care. In no case was the treatment terminated because of failure of the pump. With daily follow-up and close monitoring for development of complications, it is possible to discharge patients earlier after HDCT and PBSCT, thereby decreasing costs.
Gesehen am 21.12.2021